Sistem Informasi Ekstrakurikuler dan Prestasi Siswa SDN Tanjung Pagar 4 Banjarmasin Berbasis Web dan Email Gateway - Aulia (mijournal.org, 2026)
Extracurricular activities are one of the means used by schools to develop students' interests, talents, and abilities outside academic activities. However, the management of extracurricular and student achievement data at SDN Tanjung Pagar 4 Banjarmasin is still carried out manually using Microsoft Excel, resulting in less effective data recording, searching, and reporting processes. This study aims to develop a web-based Extracurricular and Student Achievement Information System equipped with an email gateway feature. The system was developed using the Waterfall method, which consists of requirements analysis, system design, implementation, testing, and maintenance stages. The application was developed using PHP as the programming language and MySQL as the database management system. System testing was conducted using the Black Box Testing method to ensure that all system functions operate according to user requirements. The results indicate that the developed system is capable of managing student data, supervisor data, extracurricular activities, schedules, attendance, grades, and student achievements in an integrated manner. In addition, the email gateway feature helps deliver information to the school principal more quickly and effectively. Therefore, the developed system improves the effectiveness and efficiency of managing extracurricular activities and student achievement data at SDN Tanjung Pagar 4 Banjarmasin.